The interrelationship between personal and social in health preservation under the conditions of a modern consumer society: socio-philosophical analysis (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the socio-philosophical study of a person’s health-preserving behavior in the conditions of a modern consumer society. It is clarified that the concept of «health preservation» in the conditions of the consumption society acquires a new content and new forms of manifestation.This paper deals with the interrelationship between personal and social in the health-preserving behavior of a person which is demonstrated through the fashion for the consumption of healthcare services, the complete medicalization of society, the commercialization and branding of medicine, the demonstrative consumption of the services of modern wellness industry.The article focuses on the fact that adaptation to risk factors in a consumer society, that is, the degree of resistance to socially conditioned threats to health, is directly determined by the readiness or indifference of a person to self-management by the parameters such as cognitive, motivational, emotionalvolitionaland physical.The author comes to the conclusion that the demonstration of social status or attempt to improvesocial status in the eyes of society through involvement in the consumption of healthcare services, facilitatethe formation of a new model of modern healthy behavior.The article is an attempt of the author to comprehend health and health preservation as communicativepractices that have been transformed into a specific culture of personal behavior.Key words: consumer society, health preservation, social health markers, personal health markers, health-preserving behavior, culture, spirituality